PEMBENTUKAN KARAKTER DISIPILIN SISWA DALAM BERIBADAH MELALUI PEMBIASAAN SHALAT DHUHA DI MADRASAH TSANAWIYAH AL-KHAIRIYAH PIPITAN - Malihah Cucu; Rd Hidayatullah; Moh Luthfi (Program Studi Pendidikan Agama Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2019)
The purpose of this study was to find out how the character of students discipline in the dhuha shalat worship at the Madrsah Tsanawiyah Al-Khairiyah Pipitan and to find out the factors that cause student discipline character in the dhuha prayer service. The background of this research is that there are still some students who have not been disciplinary refraction is often carried out through dhuha prayer activities. The problem formulation of this study is, 1) how is the character of student discipline in the dhuha prayer service at the Madrasah Tsanawiyah Al-Khairiyah Pipitan. 2) to find out the factora that cause the formation of students’character discipline in worship. The method used in this study is descriptive qualitativ. Data collection techniques by observation, interviews, documentatopn. While the date analysis used includes data reduction, data display, and conclusion. The conclusion of the formation of students’ disciplinary character in worship through the habit of praying dhuha in the Madrasah Tsanawiyah Al-Khairiyah Pipitan is sufficiently disciplined. This is see when students’ are disciplined in performing dhuha prayers and carrying out all the arrangements in the dhuha prayer. The factors tht couse the formation of the character of student discipline are habituation that is done repeatedly, the environment and the teacher as role models.